DAMPAK PENGELOLAAN HUTAN DESA TERHADAP SOSIAL EKONOMI MASYARAKAT NEGERI OMA, MALUKU TENGAH - Paly, Alvienly Mezli; Parera, Evelin; Iskar, Iskar (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
The social forestry program through the Village Forest scheme aims to improve community welfare while ensuring forest sustainability. However, the socio-economic effectiveness of this program remains varied, particularly in island regions. This study aims to analyze the social and economic impacts of Village Forest management and to identify the factors influencing its implementation in Negeri Oma, Central Maluku Regency. This research employed a mixed-methods approach, involving a survey of 30 respondents from Social Forestry Business Groups (KUPS), key informant interviews, field observations, and document analysis. Data were analyzed using descriptive quantitative and qualitative approaches, including data reduction, data display, and conclusion drawing. The results show that the Village Forest program has generated positive social impacts, particularly in strengthening social cohesion and mutual cooperation among community members, especially within non-timber forest product (NTFP)-based groups. However, the level of community participation remains limited and tends to be dominated by core group leaders. From an economic perspective, the program has not significantly contributed to household income, functioning only as a supplementary income source with limited business scale and low production efficiency. The main factors influencing program implementation include weak institutional capacity, limited business skills and market access, tenure conflicts—particularly in ecotourism development—and insufficient facilitation and external support. This study emphasizes that the success of Village Forest management is not solely determined by legal access to forest resources, but also by strengthening local institutions, scaling up economic activities, and ensuring sustainable market integration.